Blind analysis on the shaking table test of a 7-story reinforced concrete building using a detailed finite element model. (15th July 2022) - Mizushima, Yasunori; Kinoshita, Takuya
Abstract: Blind analysis conducted with hidden experimental data is needed to examine the accuracy of numerical model results without any arbitrary tunning. For this purpose, the National Center for Research on Earthquake Engineering in Taiwan held an international blind analysis contest for the shaking table test of a half-scale 7-story reinforced concrete building. Our analysis obtained using a detailed finite element (FE) model won the 1 st place out of 66 teams. The detailed FE model of the entire building shape was composed of solid elements for concrete parts and beam elements for reinforced bars, and bond slip was defined between the solid and beam elements. A conventional framing model was also developed to obtain the reference data. The detailed FE model reproduced the structural characteristics of the building with the hidden experimental data. The accuracy of the FE model was superior to that of the frame model in large deformation ranges. Because the supplied experimental data from the contest organizer may include the effect of shaking table rocking, removing the rocking effect can further improve the FE model. Highlights: The authors won the blind analysis contest for a shaking table test of a 7-story reinforced concrete building. The analysis was conducted using a detailed FE model that was composed of solid elements for concrete parts and beam elements for reinforced bars. The accuracy of the FE model was superior to that of the frame model in large deformation ranges. Considering the rocking effect on the experimental results can further improve the FE model.